Association of Inflammation With Pronociceptive Brain Connections in Rheumatoid Arthritis Patients With Concomitant Fibromyalgia. Issue 1 (26th November 2019) - Kaplan, Chelsea M.; Schrepf, Andrew; Ichesco, Eric; Larkin, Tony; Harte, Steven E.; Harris, Richard E.; Murray, Alison D.; Waiter, Gordon D.; Clauw, Daniel J.; Basu, Neil
Abstract : Objective: Rheumatoid arthritis (RA) patients with concomitant fibromyalgia (FM) exhibit alterations in brain connectivity synonymous with central sensitization. This study was undertaken to investigate how peripheral inflammation, the principal nociceptive stimulus in RA, interacts with brain connectivity in RA patients with FM. Methods: RA patients with concomitant FM and those without FM (FM+ and FM−, respectively; n = 27 per group) underwent functional connectivity magnetic resonance imaging. Seed‐to–whole‐brain functional connectivity analyses were conducted using seeds from the left mid/posterior insula and left inferior parietal lobule (IPL), which are regions that have been previously linked to FM symptoms and inflammation, respectively. The association between functional connectivity and erythrocyte sedimentation rate (ESR) was assessed in each group separately, followed by post hoc analyses to test for interaction effects. Cluster‐level, family‐wise error (FWE) rates were considered significant if the P value was less than 0.05. Results: The group of RA patients with FM and those without FM did not differ by age, sex, or ESR ( P > 0.2). In FM+ RA patients, increased functional connectivity of the insula–left IPL, left IPL–dorsal anterior cingulate, and left IPL–medial prefrontal cortex regions correlated with higher levels of ESR (all FWE‐corrected P < 0.05). Post hoc interaction analyses largely confirmed the relationship between ESR and connectivity changes as FM scores increased. Conclusion: We report the first neurobiologic evidence that FM in RA may be linked to peripheral inflammation via pronociceptive patterns of brain connectivity. In patients with such "bottom‐up" pain centralization, concomitant symptoms may partially respond to antiinflammatory treatments.